Management of Helicoverpa armigera (Hubner) infesting tomato using biopesticides under field condition and its effect on tomato yield (Journal of the Bangladesh Agricultural University, 2020)
The tomato fruit borer, Helicoverpa armigera (Hubner) is a very destructive insect pest of tomato affecting its yield. We, hereby, assessed four biopesticides applied individually viz. Spinosad, Emamectin benzoate, Abamectin, and Lecanicillium lecanii and a chemical insecticide (Cartap) for the management of it under field conditions and effects on tomato yield. The efficacy was evaluated based on percent fruit infestation, healthy fruits, number of healthy and infested fruits per sq. meter and yield of marketable and infested fruits (ton/ha). We have found that all the tested biopesticides significantly reduced the fruit infestation caused by H. armigera and thereafter increased the marketable yield of tomato. However, the Spinosad was found as the most effective biopesticide considering the reduction of percent fruit infestation, increasing the fruit yield and decreasing the infested fruit yield which was followed by Emamectin benzoate, Abamectin, Cartap, and L. lecanii, respectively. The highest percentage of healthy fruits (81.82%) and the lowest fruit infestation (18.18%) were recorded when the tomato plants were treated with the Spinosad. Moreover, 48.09% of fruits were protected from infestation when Spinosad was used. The highest marketable yield (24.01 ton/ha) and lowest infested yield (2.26 ton/ha) were obtained from Spinosad treated plots. The application of Emamectin benzoate, Abamectin, Cartap, and L. lecanii provided 20.77, 19.76, 15.23 and 13.67 (ton/ha) marketable yield, respectively. It is therefore concluded that the application of Spinosad performed as the most effective ones against tomato fruit borer and it could be suggested for effective management of tomato fruit borer.J Bangladesh Agril Univ 18(1): 1–5, 2020DOI: https://doi.org/10.5455/JBAU.93660